STRATEGI PENINGKATAN KUALITAS PELAYANAN JASA DENGAN MENGGUNAKAN METODE IPA (IMPORTANCE-PERFORMANCE ANALYSIS) PADA AHASS 01108 ANUGRAH JAYA SEMARANG - Kusumo, Pranedo Adhi; Sofyan, Syuhada (Faculty of Economics and Business Diponegoro University, 2016)
The background of the research is based on the failure of AHASS 01108 Anugrah Jaya Semarang to achieve targets of consumer satisfaction criteria. The objective of research is to inquire the quality of service in AHASS 01108 Anugrah Jaya in order to formulate strategies to advance the service quality. Variables used in the research are five dimensions of parasuraman quality which are tangible, reliability, responsiveness, assurance, and empathy.The population sample of the research is all of the costumers of AHASS 01108 Anugrah Jaya met during the research period. Samples in the research hence 100 respondents which were the costumers of AHASS 01108 Anugrah Jaya.Based on the calculation of appropriateness level of five dimensions of quality service, which are : tangible, empathy, reliability, responsiveness, assurance, empathy, we gained the average result of 93,33%. On the Cartesian coordinates, based on the farthest distance from the priority line, shows that Tangible 3 (waiting room facilities, etc.) becomes the main priority to be developed further in order to gain better performance of the workshop.